Issues of Openness and Flexibility for Foreign Exchange Systems. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1989)
This paper surveys briefly the main issues for official management of foreign exchange, including the choice of exchange rate regime and exchange and trade restrictive systems. It concludes by identifying the main forms of arrangements that have demonstrated their merits and practicability for developing countries in recent years, including auction and interbank exchange markets, market-based forward exchange rates, import license auctions, open general import licensing, and liberalized capital controls.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet